PCR/RFLP-based cost-effective identification of SOD2 signal (leader) sequence polymorphism (Ala-9Val) using NgoM IV: a detailed methodological approach - Akyol, O; Canatan, H; Yilmaz, HR; Yuce, H; Ozyurt, H; Sogut, S; Elyas, H (Elsevier, 2004)
Background: Superoxide dismutases (SOD) play an important role in the protection of cells and extracellular space from the products of oxidative stress. Two allelic variants have been described for the SOD2 gene (Ile58Thr involves a C to T substitution at nucleotide residue 339 and Ala-9Val involves a T to C substitution at nucleotide residue 1183). The enzyme proteins encoded by the different alleles have been suggested to have different activity patterns. Methods: The SOD2 polymorphism was determined using a polymerase chain reaction (PCR) and RFLP techniques with restriction endonuclease NgoM IV Results: The most available results were obtained from with 20 pmol primer final concentration in PCR reaction. A total of 20 pmol seems the cost-effective primer concentration with maximum quality. There were no difference between the band quality of 1-5 units of restriction endonucleases. On the other hand, short and long incubation times seem to be similar in order to obtain sharp bands on agarose gel. Conclusions: We have extended a method of SOD2 polymorphism (Ala-9Val) in mitochondrial sequence. This method provides the ability to genotype of SOD2, and it represents a fast, reliable, cost-effective and semi-automated methodology to determine SOD2 polymorphism in order to perform large-scale population studies. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: manganese superoxide dismutase; polymorphism; PCR; signal sequence